Evaluation of the impact of Shandong illegal vaccine sales incident on immunizations in China - Lei Cao; Jingshan Zheng; Lingsheng Cao; Jian Cui; Qiyou Xiao (Taylor & Francis Group, 2018)
A case of illegal vaccine sales in Shandong province, China, (hereinafter, the incident), which caused a lack of confidence among vaccination recipients and public panic, was uncovered in March 2016. We conducted a study comprising two cross-sectional surveys: at two months (May 2016) and seven months (October 2016) after the incident. The study aimed to evaluate the impact on immunizations; investigate the variation of the immunization coverage of the National Immunization Program Vaccines (NIPV) and the sales volume growth rate of Category II vaccines; and understand the reasons for non-vaccination and perspectives on immunization. The immunization coverage of NIPV decreased by 5.6 percentage points in the first survey, with a decline of 11.1 in the region of the incident, and decreased by 0.6 in the second survey compared to same period in 2015. The sales volume growth rate of Category II vaccines decreased by 25.8% in the study area and by 48.8% in the region of the incident in April 2016 compared to April 2015. Overall, 15.8% of respondents in the first survey and 7.0% in the second survey did not vaccinate their children according to the NIPV schedule because of the incident (χ2 = 78.463, P < 0.05). The vaccination was likely affected by the incident in varying degrees, especially in the involved region and particularly in relation to Category II vaccines. Overall, 34% of respondents avoided Category II vaccines for their children, indicating that it will take considerable time to eliminate the negative stigma associated with the incident.